APHORISMS FROM THE BOOK BY MARY SHELLEY “FRANKENSTEIN. THE MODERN PROMETHEUS” - Nurkhanova, M.A. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
The present article focuses on aphorisms, which are still a disputable notion in linguistic sphere due to the following factors: the absence of a generally accepted definition of the aphorism, the indistinguishable varieties of the aphorism and its related phenomena, the multiplicity of the use of the aphorisms and the variety of their functions in belles-lettres. The aphorism is a multidimensional phenomenon; The study of aphorisms is important not only for linguistics (especially for disciplines such as stylistics and rhetoric), but also for literature and other humanities disciplines. We believe the book by Mary Shelley has not yet been sufficiently investigated from the point of phraseology and excerpts from this book that have developped into aphorisms deserve a close study.. Hopefully, as a result of this research , the author’s deeply sensual thoughts would be revealed to people reading classics.
Keywords: aphorism; definition of aphorism; quotes; Mary Shelley; Frankenstein; novel; function of aphorisms